Comparison of Clinical Characteristics and Short-Term Prognoses Within Hospitalized Chronic Obstructive Pulmonary Disease Patients Comorbid With Asthma, Bronchiectasis, and Their Overlaps: Findings From the ACURE Registry - Lei, Jieping; Yang, Ting; Liang, Chen; Huang, Ke; Wu, Sinan; Wang, Chen (Frontiers in Medicine, 2022)
Introduction: Real-world evidence and comparison among commonly seen chronic obstructive pulmonary disease (COPD) phenotypes, i.e. asthma-COPD overlap (ACO), bronchiectasis-COPD overlap (BCO), and their coexistence (ABCO) have not been fully depicted, especially in Chinese patients. Methods: Data were retrieved from an ongoing nationwide registry in hospitalized patients due to acute exacerbation of chronic obstructive pulmonary disease in China (ACURE). Results: Of eligible 4,813 COPD patients, 338 (7.02%), 492 (10.22%) and 63 (1.31%) were identified as ACO, BCO and ABCO phenotypes, respectively. Relatively, the ABCO phenotype had a younger age with a median of 62.99 years (interquartile range (IQR): 55.93-69.48), and the COPD phenotype had an older age with a median of 70.15 years (IQR: 64.37-76.82). The BCO and COPD phenotypes were slimer in body mass index with a median of 21.79 kg/m2 (IQR: 19.47-23.97) and 21.79 kg/m2 (IQR: 19.49-24.22), respectively. The COPD phenotype had more male gender (79.90%) and smokers (71.12%) with a longer history of smoking (median: 32.45 years, IQR: 0.00-43.91). The ACO and ABCO phenotypes suffered more prior allergic episodes with a proportion of 18.05% and 19.05%, respectively. The ACO phenotype exhibited a higher level of eosinophil and better lung reversibility. Moreover, the four phenotypes showed no significant difference in all-cause mortality, intensive care unit admission, length of hospital stay and COPD Assessment Test score change during the index hospitalization, and neither in the day 30 outcomes, i.e. all-cause mortality, recurrence of exacerbation, all-cause and exacerbation-related readmission. Conclusions: The ACO, BCO, ABCO and COPD phenotypes exhibited distinct clinical features but had no varied short-term prognoses. Further validation in a larger sample is warranted.